2018
DOI: 10.1002/hed.25086
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck lymphedema management: Evaluation of a therapy program

Abstract: This pilot study found a reduction in head and neck lymphedema over the 22-week lymphedema treatment course. This intervention may be successful in reducing head and neck lymphedema; however, further studies are needed to investigate these findings in a larger sample with the use of a control group to negate improvements from healing over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 15 publications
0
60
0
Order By: Relevance
“…17,18 A change of one level, for example, 1b to 1a, was understood to be a clinically relevant change. 14 Module (EORTC QLQ-H&N43). 19 The EORTC QLQ-H&N43 contains the core 30 questions from the EORTC QLQ-C30 version three and an additional 43 questions measuring QOL in patients with head and neck cancer.…”
Section: Assessment Of Lymphedemamentioning
confidence: 99%
See 4 more Smart Citations
“…17,18 A change of one level, for example, 1b to 1a, was understood to be a clinically relevant change. 14 Module (EORTC QLQ-H&N43). 19 The EORTC QLQ-H&N43 contains the core 30 questions from the EORTC QLQ-C30 version three and an additional 43 questions measuring QOL in patients with head and neck cancer.…”
Section: Assessment Of Lymphedemamentioning
confidence: 99%
“…T A B L E 3 Individual participant scores for the control and intervention groups on lymphedema measures at baseline (T0) and follow-up (T1) The MCID reference for this study was the use of the MDACCHNL Rating Scale. 14 The authors found this measure highly subjective and difficult to categorize as many participants presented with both fibrotic and soft edema in different regions. A recent study using the MDACCHNL rating scale as the MCID stated that it was useful in supporting the reduction in lymphedema, however, is a generous measure for the use of a MCID.…”
Section: Body Image Swallowing and Qolmentioning
confidence: 99%
See 3 more Smart Citations